2019
DOI: 10.1002/jcph.1423
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Drug‐Drug Interactions Between Letermovir and the Immunosuppressants Cyclosporine, Tacrolimus, Sirolimus, and Mycophenolate Mofetil

Abstract: Letermovir (AIC246, MK‐8228) is a human cytomegalovirus terminase inhibitor indicated for the prophylaxis of cytomegalovirus infection and disease in allogeneic hematopoietic stem cell transplant recipients that is also being investigated for use in other transplant settings. Many transplant patients receive immunosuppressant drugs, of which several have narrow therapeutic ranges. There is a potential for the coadministration of letermovir with these agents, and any potential effect on their pharmacokinetics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 15 publications
6
88
1
Order By: Relevance
“…33 This observed effect is likely due to cyclosporine inhibiting the liver uptake transporters OATP1B1/3, which are responsible for letermovir elimination, and supports the dose adjustment to 240 mg of letermovir when given concomitantly. 33 Lastly, the co-administration of letermovir with mycophenolate mofetil had no meaningful effect on the pharmacokinetics of mycophenolate mofetil, and vice versa. 33 Posaconazole and voriconazole are commonly used in HCT patients to prevent opportunistic fungal infections.…”
Section: Pharmacokineticssupporting
confidence: 52%
See 1 more Smart Citation
“…33 This observed effect is likely due to cyclosporine inhibiting the liver uptake transporters OATP1B1/3, which are responsible for letermovir elimination, and supports the dose adjustment to 240 mg of letermovir when given concomitantly. 33 Lastly, the co-administration of letermovir with mycophenolate mofetil had no meaningful effect on the pharmacokinetics of mycophenolate mofetil, and vice versa. 33 Posaconazole and voriconazole are commonly used in HCT patients to prevent opportunistic fungal infections.…”
Section: Pharmacokineticssupporting
confidence: 52%
“…33 Lastly, the co-administration of letermovir with mycophenolate mofetil had no meaningful effect on the pharmacokinetics of mycophenolate mofetil, and vice versa. 33 Posaconazole and voriconazole are commonly used in HCT patients to prevent opportunistic fungal infections. Two pharmacokinetic trials conducted in healthy female subjects evaluated the interactions between these azole antifungals and 480 mg of letermovir.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Data are expressed as Data are expressed as mean ± SD for normally distributed continuous variables, median (25, 75% interquartile range) for abnormal distributed continuous variables or number (percentage). In a previous study, the co-administration of LMV at clinical doses with TAC resulted in a 2.4-fold increase in the area under the plasma TAC concentration-time curve and a 1.6-fold increase in the maximum plasma TAC concentration in 14 healthy female participants [20]. This was because TAC is predominantly metabolized by CYP3A4 [13] and LMV is a moderate inhibitor of CYP3A4 [18].…”
Section: Discussionmentioning
confidence: 95%
“…It is a weak-to-moderate inhibitor of CYP3A4 and a weak-to-moderate inducer of CYP2C9 and CYP2C19 [18]. The interaction between LMV and TAC has been assessed in healthy participants, and LMV was found to increase TAC exposure [19,20]. The interaction between LMV and VRCZ has also been assessed in healthy participants, and it was found that LMV decreases VRCZ exposure [21].…”
Section: Ivyspringmentioning
confidence: 99%
“…Letermovir decreases voriconazole levels by inducing CYP2C9/19, but does not alter posaconazole levels [8]. Coadministration of letermovir with cyclosporine, tacrolimus and sirolimus leads to increased exposure to these immunosuppressive drugs; therefore, a dose of 240 mg daily is suggested if cyclosporine is co-administered [9]. In contrast, letermovir does not alter exposure to mycophenolate.…”
Section: Letermovir-a Novel Drug For Cytomegalovirus Prophylaxismentioning
confidence: 99%